Peran dan Tantangan Sistem Informasi Manajemen dalam Mendukung Kinerja Perusahaan di Era Digital: Kajian Literatur - Alika Putri; Magdalena Mori Sihotang; Valentina Rentauli Siringoringo; Muhammad Ridha Habibi Z (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
In the digital era, Management Information Systems (MIS) play a vital role not only as administrative tools but also as strategic instruments to enhance efficiency, decision-making, and organizational competitiveness. This study employs a systematic literature review to examine the roles and challenges of MIS in supporting firm performance. The findings reveal that MIS facilitates cross-functional coordination, provides real-time information, and supports digital transformation. However, challenges remain, including legacy system integration, limited digital literacy, organizational resistance, and data security issues. Therefore, effective MIS implementation requires a holistic approach that integrates technology, human resources, and data governance. This study contributes theoretically to the development of MIS literature and offers practical recommendations for organizations to maximize the benefits of MIS in the digital era